Determining Stock Returns for the LQ45 Index on the Indonesia Stock Exchange - Khalqi, Muhammad; Handoyo, Sarwo Edy (Journal Research of Social Science, Economics, and Management, 2026)
For a country, capital markets play a crucial role in maintaining capital flows and economic activity. Therefore, investing in capital markets requires numerous considerations. This study aims to identify factors that influence returns. Shares of companies listed on the LQ45 Index on the Indonesia Stock Exchange from 2023 to 2025. The independent variable in this study is Return on Assets (ROA). Return on Equity (ROE), Price to Book Value (PBV), Debt to Equity Ratio (DER) and Market Capitalization, while the dependent variable is Return Stocks. This study uses panel data using a purposive sampling method that produces 90 samples. Panel data regression analysis used Fixed Effect Model (FEM). The results of this study indicate that Price to Book Value (PBV) has a significant and negative influence against Return Stocks and Market Capitalization has a significant and positive influence on Return Stocks. Meanwhile, Return on Equity (ROE) and Debt to Equity Ratio (DER) does not have a significant effect on Return Stocks. This study confirms that in the 2023-2025 period, investors in companies listed in the LQ45 Index prioritized company value over profitability and existing capital structure. These findings are expected to provide practical insights for investors and other stakeholders in the capital market.